Ecological momentary assessment for chronic pain in fibromyalgia using a smartphone: A randomized crossover study. (22nd November 2013) - Garcia‐Palacios, A.; Herrero, R.; Belmonte, M.A.; Castilla, D.; Guixeres, J.; Molinari, G.; Baños, R.M.; Botella, C.
Abstract Background Daily diaries are a useful way of measuring fluctuations in pain‐related symptoms. However, traditional diaries do not assure the gathering of data in real time, not solving the problem of retrospective assessment. Ecological momentary assessment (EMA) by means of electronic diaries helps to improve repeated assessment. However, it is important to test its feasibility in specific populations in order to reach a wider number of people who could benefit from these procedures. Methods The present study compares the compliance and acceptability of an electronic diary running on a smartphone using a crossover design for a sample with a specific pain condition, fibromyalgia and low familiarity with technology. Forty‐seven participants were randomly assigned to one of two conditions: (1) paper diary – smartphone diary and (2) smartphone diary – paper diary, using each assessment method for 1 week. Results The findings of this study showed that the smartphone diary made it possible to gather more accurate and complete ratings. Besides, this method was well accepted by a sample of patients with fibromyalgia referred by a public hospital, with an important proportion of participants with low level of education and low familiarity with technology. Conclusions The findings of this study support the use of smartphones for EMA even in specific populations with a specific pain condition, fibromyalgia and with low familiarity with technology. These methods could help clinicians and researchers to gather more accurate ratings of relevant pain‐related variables even in populations with low familiarity with technology.